Notch-1 Inhibition Promotes Immune Regulation in Transplantation Via Regulatory T Cell–Dependent Mechanisms. Issue 10 (3rd September 2019) - Magee, Ciara N.; Murakami, Naoka; Borges, Thiago J.; Shimizu, Tetsunosuke; Safa, Kassem; Ohori, Shunsuke; Cai, Songjie; Uffing, Audrey; Azzi, Jamil; Elyaman, Wassim; Charbonnier, Louis-Marie; Liu, Kaifeng; et al.
Abstract : Background: Transplantation is the treatment of choice for many patients with end-stage organ disease. Despite advances in immunosuppression, long-term outcomes remain suboptimal, hampered by drug toxicity and immune-mediated injury, the leading cause of late graft loss. The development of therapies that promote regulation while suppressing effector immunity is imperative to improve graft survival and minimize conventional immunosuppression. Notch signaling is a highly conserved pathway pivotal to T-cell differentiation and function, rendering it a target of interest in efforts to manipulate T cell–mediated immunity. Methods: We investigated the pattern of Notch-1 expression in effector and regulatory T cells (Tregs) in both murine and human recipients of a solid-organ transplant. Using a selective human anti-Notch-1 antibody (aNotch-1), we examined the effect of Notch-1 receptor inhibition in full major histocompatibility complex–mismatch murine cardiac and lung transplant models, and in a humanized skin transplant model. On the basis of our findings, we further used a genetic approach to investigate the effect of selective Notch-1 inhibition in Tregs. Results: We observed an increased proportion of Tregs expressing surface and intracellular (activated) Notch-1 in comparison with conventional T cells, both in mice with transplants and in the peripheral blood of patients with transplants. In the murine cardiac transplant model, peritransplant administration of aNotch-1 (days 0, 2, 4, 6, 8, and 10) significantly prolonged allograft survival in comparison with immunoglobulin G–treated controls. Similarly, aNotch-1 treatment improved both histological and functional outcomes in the murine lung transplant model. The use of aNotch-1 resulted in a reduced proportion of both splenic and intragraft conventional T cells, while increasing the proportion of Tregs. Furthermore, Tregs isolated from aNotch-1–treated mice showed enhanced suppressive function on a per-cell basis, confirmed with selective Notch-1 deletion in Tregs (Foxp3 EGFPCre Notch1 fl/fl ). Notch-1 blockade inhibited the mammalian target of rapamycin pathway and increased the phosphorylation of STAT5 (signal transducer and activator of transcription 5) in murine Tregs. Notch-1 low Tregs isolated from human peripheral blood exhibited more potent suppressive capacity than Notch-1 high Tregs. Last, the combination of aNotch-1 with costimulation blockade induced long-term tolerance in a cardiac transplant model, and this tolerance was dependent on CTLA-4 (cytotoxic T-lymphocyte–associated antigen-4) signaling. Conclusions: Our data reveal a promising, clinically relevant approach for immune modulation in transplantation by selectively targeting Notch-1. Abstract : Supplemental Digital Content is available in the text.